Condiciones turísticas y el desarrollo del turismo de aventura en el recreo turístico Casa de ayahuasca, 2022 - Arevalo Villacorta, Gabriela (2023)
The objective of the research was to determine the relationship between tourist conditions and the development of tourism, whose type of study was descriptive-correlational, which is why the behavior of the variables was analyzed and described, to later determine the relationship, it was also of non-experimental design with a population and sample made up of 296 visitors, to whom a survey was applied, obtaining as a result that the tourist conditions of the tourist recreation are regular, due to the existence of shortcomings evidenced by the visitor, such as little conservation of natural resources, the limited categorization, the few cultural manifestations, and the few natural spaces that are in good condition. On the other hand, it was identified that the development of adventure tourism obtained an average result, due to the deficiencies found in the planning and management process developed by the administration of the place, the inadequate territorial conditioning, which hinder the tourist purposes, among others. factors that impede the growth and sustainability of recreation. Finally, it was determined that there is a relationship between the study variables, contrasted by a coefficient of 0.738 and a (bilateral) significance of 0.000.